Chrysostom’s reception of Luke 19:8b (the declaration of Zacchaeus) - Ronald H. van der Bergh (HTS Teologiese Studies/Theological Studies, 2014)
This article investigates the reception of Luke 19:8b in the works of Chrysostom. The ambiguous nature of Luke 19:8b in its Lukan context provides a glimpse into Chrysostom’s thoughts on this passage. In asking the question of how Chrysostom viewed Zacchaeus’s salvation to be effected (cf. the direct speech of Jesus in Luke 19:9−10), the article demonstrates that Chrysostom’s consistent concern, wherever reference to Luke 19:8b is made, is with adequate compensation to people who have been wronged. The article also points out how Chrysostom did not shy away from making slight changes to the biblical narrative to convey this message.